Síntese, caracterização e reatividade química de Heterociclos carbonilados funcionalizados através de Reações de acoplamento cruzado - Araújo, Rodrigo Santos Aquino de (2016)
Natural compounds, as coumarins and others oxygenated heterocycles, has been shown with a rich source of bioactive substances, however, due to difficulty of getting into large amounts of these substances isolated, many total synthesis or semi-synthesis methods has been developed. Among these many synthetic derivation strategies currently, the metal-catalyzed cross-coupling reactions have been highlighted in the literature, such as: Suzuki-Miyaura, Sonogashira, Heck, Negishi and Buchwald-Hartwig. In the present work, it is aimed the obtaining and preparation of natural heterocycles skeleton, and your derivations via cross-coupling palladium-catalyzed reactions; of which were obtained excellent results for the first three mentioned above, which was not repeated for the last two protocols, from the reactional conditions used. In all synthetics strategies realized, reactional conditions were diversify, such as temperature, reactional time, energy source, base, catalysts, among others; with the in order to observe the effects these changes and obtain the best sets of conditions. Besides the palladium-catalyzed reactions, some of cumarinic alkynes obtained by Sonogashira were submitted to the catalytic hydrogenation, to provide new alkanes with different spacers between the coumarinic ring and their phenyl groups. In general, the final compounds obtained showed from good to great yield values, reflecting on success in mostprotocols tested, where a total of 48 final molecules were obtained, of which 26 are novel compounds, all being characterized and proven according to their chemical structures.